Maternal tea consumption and the risk of preterm delivery in urban China: a birth cohort study - Lei Huang; Catherine Lerro; Tao Yang; Jing Li; Jie Qiu; Weitao Qiu; Xiaochun He; Hongmei Cui; Ling Lv; Ruifeng Xu; Xiaoying Xu; Huang Huang; et al. (BMC, 2016)
Abstract Background Studies investigating the relationship between maternal tea drinking and risk of preterm birth have reached inconsistent results. Methods The present study analyzed data from a birth cohort study including 10,179 women who delivered a singleton live birth were conducted in Lanzhou, China between 2010 and 2012. Results Drinking tea (OR = 1.36, 95 % CI: 1.09-1.69), and specifically green (OR = 1.42, 95 % CI: 1.08-1.85) or scented tea (OR = 1.61, 95 % CI: 1.04-2.50), was associated with an increased risk of preterm birth. Drinking tea was associated with both moderate preterm (OR = 1.41, 95 % CI: 1.12-1.79) and spontaneous preterm birth (OR = 1.41, 95 % CI: 1.09-1.83). Risk of preterm birth increased with decreasing age of starting tea drinking (<20 years, OR = 1.60, 95 % CI: 1.17-2.20) and increasing duration (p for trend < 0.01). The relationship between tea drinking and preterm birth is modified by both maternal age (p < 0.05) and gestational weight gain (p < 0.05). Conclusions Despite conflicting findings in the previous literature, we saw a significant association with maternal tea drinking and risk of preterm birth in our cohort. More studies are needed both to confirm this finding and to elucidate the mechanism behind this association.